Will neuropriming be a game-changer for sport performance? - Chao, D. (2017)
For all the advances in training and preparation, brain performance is still an area that can leave coaches stumped. Most in sport accept that the brain can be harnessed to accelerate learning and improve performance but there is little collective understanding of how. The neurological space represents a `greenfield opportunity`, according to Halo Neuroscience Co-Founder Daniel Chao, as the sport continues to comprehend the importance of the brain.